ANALISIS POTENTIAL LOSS PENERIMAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - FLADONA RIZOLA, B61112049 (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT Â  Thesis titled â€œAnalysis of Potential Loss Perolehan Hak Atas Tanah dan Bangunan (BPHTB) in Sungai Raya Distric of Kubu Raya Regencyâ€ is a very important academic research. Data of tax income in Kubu Raya regency in 2011-2013 shown that the BPHTB income about 60% of total of tax income. However, there is no study conducted to know whether the BPHTB is optimal. Â  The analysis of potensial loss of BPHTB is conducted in Sungai Raya Subdistrict, Kubu Raya Regency. This study is conducted based on empirical data collected via observation and the data collected at government agency speciallyÂ  Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah Kubu Raya Regency. Â  The objective of this study to reveal the potential loss of BPHTB income in Sungai Raya Subdistrict and to develop strategies that should be done by Kubu Raya Regency to optimise the BPHTB income as the regional income. Â  The method adopted in this thesis is â€œDescriptive Analysisâ€ by using secondary and primary data. The BPHTB income that be collceted by Dinas Pendapatan Pengelolaan Keuangan dan Aset Daerah Kubu Raya Regency is compared with potential income of BPHTB specially at Subdistrict Sungai Raya, Kubu Raya Regency, thus the level of potential loss could be determined. The cause of income potential loss is revealed by observation. The strategies to increase the BPHTB income is developed using SWOT Analysis and SWOT Matrix. Â  The results show that BPHTB income at Sungai Raya Subdistrict, Kubu Raya Regency has potential loss. The strategy that should be done to increase the original regional income from tax sector specially BPHTB are strength-opportunity strategy: using the decentralised income policy based on Central or Regional Regulation and also by utilized the opportunity to increase the regional income specially BPHTB. The strategies include: (1) to re-new Nilai Jual Objek Pajak (NJOP) Pajak Bumi dan Bangunan Pedesaan dan Perkotaan (PBB-P2) as a basis of minimum value of BPHTB; (2) approach and cooperate related agencies; (3) conduct tax campaign; (4) improve skill of the tax staff; (5) improve the organization structure that more focus on the tax service; (6) improve the attention of regency government by giving reward the good tax payer that pay the tax on time.Â